ICT Update 66: A future for telecentres - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
ICT Update is a bimonthly printed and on-line magazine (http://ictupdate.cta.int) and an accompanying e-mail newsletter published by CTA. This issue focuses on the future of telecentres.